Topoisomerase II Poisons for Glioblastoma; Existing Challenges and Opportunities to Personalize Therapy - Mehta, Amol; Awah, Chidiebere U.; Sonabend, Adam M. (Frontiers in Neurology, 2018)
Despite advances in surgery, radiotherapy, and chemotherapy, glioblastoma (GBM) remains a malignancy with poor prognosis. The molecular profile of GBM is diverse across patients, and individual responses to therapy are highly variable. Yet, patients diagnosed with GBM are treated with a rather uniform paradigm. Exploiting these molecular differences and inter-individual responses to therapy may present an opportunity to improve the otherwise bleak prognosis of patients with GBM. This review aims to examine one group of chemotherapeutics: Topoisomerase 2 (TOP2) poisons, a class of drugs that enables TOP2 to induce DNA damage, but interferes with its ability to repair it. These potent chemotherapeutic agents are currently used for a number of malignancies and have shown promise in the treatment of GBM. Despite their robust efficacy in-vitro, some of these agents have fallen short of achieving similar results in clinical trials for this tumor. In this review, we explore reasons for this discrepancy, focusing on drug delivery and individual susceptibility differences as challenges for effective TOP2-targeting for GBM. We critically review the evidence implicating genes in susceptibility to TOP2 poisons and categorize this evidence as experimental, correlative or both. This is important as mere experimental evidence does not necessarily lead to identification of genes that serve as good biomarkers of susceptibility for personalizing the use of these drugs.